Effect Of Firm Size, Debt Equity Ratio and Current Ratio to Return on Asset (Study on Hotel, Restaurant and Tourism Companies Listed on IDX) - Adhi Widyakto; M. Sigit Taruna; Fredericho Mego Sundoro (Universitas Semarang, 2022)
This research aims to find out the influence of Firm Size, Debt Equity Ratio (DER), and Current Ratio (CR) on Return on Assets (ROA) on hotel, restaurant and tourism companies listed on Indonesia Stock Exchange (IDX). Research on profitability in companies engaged in the tourism sector is necessary because currently, the sector has a high opportunity to move the community's economy. This research will reveal variations in the role of company size, solvability, and liquidity to profitability in the tourism sector. The sample used in this study amounted to 10 of the 48 Hotel, Restaurant, and Tourism sub-sector companies listed on the IDX in the period 2018-2020. The selection of such samples using purposive sampling techniques, in which researchers set specific provisions tailored to the purpose of the study. The data analysis techniques used are multiple linear regression, classical assumption test, t-test, F test and coefficient of determination. Based on simultaneous tests, it was found that the variables Firm Size, Debt Equity Ratio (DER), and Current Ratio (CR) significantly affect the return on asset (ROA) in hotel, restaurant and tourism sub-sectors listed on the IDX. Penelitian ini bertujuan untuk mengetahui pengaruh Ukuran Perusahaan, Debt Equity Ratio (DER), Current Ratio (CR) terhadap Return on Assets (ROA) pada perusahaan hotel, restoran dan pariwisata yang terdaftar di Bursa Efek Indonesia (BEI). Penelitian tentang profitabilitas pada perusahaan yang bergerak disektor pariwisata sangat perlu dilakukan. Sektor ini memiliki peluang tinggi dalam menggerakkan perekonomian masyarakat. Penelitian ini akan mengungkap variasi peran ukuran perusahaan, sovabilitas, dan likuiditas terhadap profitabilitas dalam sector pariwisata. Sampel yang digunakan dalam penelitian ini berjumlah 10 dari 48 perusahaan subsektor Hotel, Restoran, dan Pariwisata yang terdaftar di BEI periode 2018-2020. Pemilihan sampel tersebut menggunakan teknik purposive sampling, dimana peneliti menetapkan ketentuan tertentu yang disesuaikan dengan tujuan penelitian. Teknik analisis data yang digunakan adalah regresi linier berganda, uji asumsi klasik, uji t, uji F dan koefisien determinasi. Berdasarkan pengujian simultan ditemukan bahwa variabel Firm Size, Debt Equity Ratio (DER), Current Ratio (CR) berpengaruh signifikan terhadap return on asset (ROA) pada subsektor hotel, restoran dan pariwisata yang terdaftar di BEI.